Necropolitics in the Andes: Reading the Senderista As Sovereign Subject or As Subject of Sovereignty in Two Peruvian Novels - Hunt, Rosanna (Bulletin of Spanish studies (2002), 2020)
This paper discusses ways in which literary representations of senderistas strive to humanise the figure of the necropolitically-defined state 'enemy' and do so within the broad moment of neoliberal consensus-building around the friend-enemy division in Peru. Drawing on Achille Mbembe's reformulation of biopolitics, the paper offers close readings of Vargas Llosa's Lituma en los Andes (1994) and Roncagliolo's Abril rojo (2006). Where Vargas Llosa's rehumanising of the individual senderista leaves the absolutely enmity of Sendero Luminoso as 'terror' intact, Roncagliolo recasts the senderista as an irreducibly complex subject defined as much as victim as perpetrator of violence.